Increasing gender diversity in senior roles in HE: Who is afraid of positive action? - Simonetta Manfredi (Administrative Sciences, 2017)
This article argues that Higher Education Institutions should adopt positive action in recruitment and promotion to tackle women's under-representation in senior leadership roles. In a tie-break situation where two candidates are "as qualified as each other", section 159 of the UK Equality Act 2010 allows employers to give preference to a candidate from an under-represented group. The use of this measure, however, is often contested on the grounds that it is a form of reverse discrimination, it is tokenistic and that it can undermine meritocracy. This article seeks to challenge these objections and suggests that, far from undermining meritocracy, the use of positive action in recruitment and promotion could prove a useful tool to tackle gender bias, unpack stereotypes and re-appraise how merit is defined and assessed.
Keywords: 350; gender diversity; leadership; higher education; positive